FLAVONOID CONTENTS, ANTIOXIDANT AND NEUROPROTECTIVE ACTIVITY OF EXTRACTS OF RUSSIAN PLANTS - Klochkov, S.; Bachurin, S.; Shevtsova, E.; Novikova, O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plant flavonoids cause active interest in connection with their authentic influence on the decrease of the risk of cardiovascular diseases and with their potential neuroprotective properties. Antioxidant and free radical-scavenging abilities of flavonoids can be a basis of positive effects of many plant extracts (1). The aim of our work was to study interrelation of antioxidant and neuroprotective activity with the contents and structure of flavonoids in plants extracts. About 200 extracts were investigated. In extracts we defined general flavonoid content and antioxidant activity. HPLC–ESI-MS/MS was used to study flavonoids in the extracts. Analysis of the interaction of plant extracts and isolation by HPLC of pure flavonoids with the mitochondria was done the following way: we defined the influence on calcium- and t-butylhydroxyperoxide-induced occurrence of lipid peroxidation and mitochondrial membrane permeability transition (MMPT). Three basic structural requirements for the presence of antioxidant activity - hydroxylated C3, an unsaturated C ring, and hydrophobicity were defined. Influence on calcium- and t-butylhydroxyperoxide-induced MMPT of plant extracts has complex concentration dependence. It was authentically shown, that extracts of plants and individual flavonoids reduce lipid peroxidation in mitochondria irrespective of used substrates of breath as in conditions of “ageing mitochondria in vitro ”, and at the presence of t-butylhydroxyperoxide. We also investigated the influence of flavonoid-rich plant extracts on glutamate-induced neurotoxicity. Some extracts inhibit MMPT and Ca2+-induced swelling with an IC50 similar to MK-801, a known antagonist of glutamate receptors, and they protect rat brain neurons in culture from glutamate toxic action. References: 1. Dean et al. Open Natural Products Journal, 2008, 1, 1-6